Relationship between Empathy and Burnout Levels of Professionals Working in Special Education and Rehabilitation Centers - Kaçan, Havva; Sakız, Halis (Current Approaches in Psychiatry, 2024)
Objective: The aim of this study is to examine the relationship between empathy and burnout levels of professionals working in special education and rehabilitation centers. Method: The sample of this descriptive-correlational study included 120 employees who agreed to participate in the study and worked in three special education and rehabilitation centers located in a city center in Northern Turkey in the 2022–2023 academic year. Data were collected using an employee identification form, the Emphatic Tendency Scale (ETS) and the Maslach Burnout Inventory (MBI). Results: Empathic tendency increased the level of emotional exhaustion (ß =.558) and depersonalization (ß =.516) but decreased the level of sense of personal accomplishment (ß=-0.655). There was a significant positive moderate relationship between the ETS score and the MBI emotional exhaustion and depersonalization subdimension scores and a significant negative moderate relationship between the feeling of personal accomplishment subdimension of MBI. Conclusion: High empathy in employees can improve the quality of support provided to students with special needs, but it can also bring challenges such as emotional exhaustion and decreased personal accomplishment.
Keywords: Mental Health Nursing; Burnout; empathy; special education and reabailitation; Tükenmişlik; empati; özel eğitim ve rehabilitasyom nerkezi; Ruh Sağlığı Hemşireliği